2019
DOI: 10.1038/s41598-019-44827-7
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PSORS1C3 is regulated by glucocorticoids and fine-tunes OCT4 expression in non-pluripotent cells

Abstract: OCT4 is a transcription factor known for its regulatory roles in stemness, tumorigenesis and stress response. Considering its versatile functions, expression of OCT4 is regulated at different levels. PSORS1C3, a long non-coding RNA overlapped with OCT4, has a putative association with immune mediated diseases; however, its exact functions remained to be elucidated. Here, we demonstrated that PSORS1C3 is regulated by glucocorticoids (GC), has two endogenously active promoters, promoter 0 and 1, and two sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Our in-silico studies revealed two potential promoters in addition to the previously known miRNAs precursor promoter [12], as well as two groups of long and short transcripts for C1orf132. The reason for generating short and long transcripts of the gene is not known, however, we observed a similar pattern of short and long transcripts for PSORS1C3 lncRNA in our previous study [17]. There is a possibility that this kind of gene expression regulation by alternative splicing in a tissue-and cell-specific manner is a more general feature of lncRNAs, and their possible dysregulation could contribute to pathogenesis of many cancers [18].…”
Section: Discussionsupporting
confidence: 75%
“…Our in-silico studies revealed two potential promoters in addition to the previously known miRNAs precursor promoter [12], as well as two groups of long and short transcripts for C1orf132. The reason for generating short and long transcripts of the gene is not known, however, we observed a similar pattern of short and long transcripts for PSORS1C3 lncRNA in our previous study [17]. There is a possibility that this kind of gene expression regulation by alternative splicing in a tissue-and cell-specific manner is a more general feature of lncRNAs, and their possible dysregulation could contribute to pathogenesis of many cancers [18].…”
Section: Discussionsupporting
confidence: 75%
“…However, it is unclear which of these are responsible for its therapeutic effect. Studies have suggested that non-coding RNAs, such as miRNAs and lncRNAs, could inhibit inflammatory diseases (Stagakis et al, 2011;Liu et al, 2020) and MP has been shown to regulate the expression of non-coding RNAs to inhibit specific proinflammatory targets (Davis et al, 2013;Mirzadeh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Perry et al 34 investigated lncRNA expression after dexamethasone treatment of primary airway smooth muscle cells and verified a dramatic change in their expression profile, with 27 lncRNAs increased and 39 decreased after treatment. Moreover, dexamethasone regulates the expression of PSORS1C3, a psoriasis‐related lncRNA 35 . In an animal model, T cells from mice treated with Δ9‐tetrahydrocannabinol (THC) showed differential expression of several lncRNAs 36 .…”
Section: Long Noncoding Rnas and Doping Detectionmentioning
confidence: 99%